HISTOMORPHOLOGICAL STUDIES ON THE NEUROSECRETORY CELLS IN THE BRAIN OF THE BEETLE CYBISTER TRIPUNCTATUS (OL) (COLEOPTERA: DYTISCIDAE) - U. S. INDURKAR; D. B. TEMBHARE (The Bioscan, 2012)
The cephalic neuroendocrine system is well developed in the adult water beetle, Cybister tripuntatus, consisting of the neurosecretory cells in the brain, corpora cardiaca and carpora allata. The brain is well distinct, bilobed structure situated on mid-dorsally on the pharynx in the head of adult beetle. The neurosecretory cells are distributed symmetrically and distinguished into five-paired groups viz. medial, lateral, ventral, posterior and optic in each hemisphere of the brain.